Long-term Effects of Parents’ Education on Children’s Educational and Occupational Success: Mediation by Family Interactions, Child Aggression, and Teenage Aspirations - Dubow, Eric F. (2009)
We examine the prediction of individuals’ educational and occupational success at age 48 from contextual and personal variables assessed during their middle childhood and late adolescence. We focus particularly on the predictive role of the parents’ educational level during middle childhood, controlling for other indices of socioeconomic status and children’s IQ, and the mediating roles of negative family interactions, childhood behavior, and late adolescent aspirations. Data come from the Columbia County Longitudinal Study, which began in 1960 when all 856 third graders in a semi-rural county in New York State were interviewed along with their parents; participants were reinterviewed at ages 19, 30, and 48 (Eron et al, 1971; Huesmann et al., 2002). Parents’ educational level when the child was 8 years old significantly predicted educational and occupational success for the child 40 years later. Structural models showed that parental educational level had no direct effects on child educational level or occupational prestige at age 48 but had significant indirect effects that were independent of the other predictor variables’ effects. These indirect effects were mediated through age 19 educational aspirations and age 19 educational level. These results provide strong support for the unique predictive role of parental education on adult outcomes 40 years later and underscore the developmental importance of mediators of parent education effects such as late adolescent achievement and achievement-related aspirations.